2012
DOI: 10.1155/2012/180103
|View full text |Cite
|
Sign up to set email alerts
|

HPTLC Fingerprint Profile and Isolation of Marker Compound of Ruellia tuberosa

Abstract: The present study was aimed to identification, isolation, and quantification of marker in R. tuberosa (Acanthaceae). HPTLC fingerprinting was carried out for various extract of root, stem, and leaf of R. tuberosa. From the HPTLC fingerprint the florescent band (under 366 nm) at R f : 0.56 (mobile phase chloroform : toluene : ethyl acetate (6 : 3 : 1, v/v)) was found in leaf, root, and stem of R. tuberosa. So, the florescent band (under 366 nm) at R f : 0.56 was isolated as marker compound RT-F2 from root of R.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 15 publications
(12 reference statements)
0
12
0
1
Order By: Relevance
“…HPTLC fingerprinting profile with biomarker is an important tool for the identification and the standardization of medicinal plants. [10] Owing to its high separation power, performance and reproducibility, it is considered superior to classical TLC. Naringin is a flavanone glycoside formed from the flavanone naringenin and the disaccharide neohesperidose, [11] is identified as a marker phytochemical in the plant Drynaria quercifolia (L.) J. Sm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HPTLC fingerprinting profile with biomarker is an important tool for the identification and the standardization of medicinal plants. [10] Owing to its high separation power, performance and reproducibility, it is considered superior to classical TLC. Naringin is a flavanone glycoside formed from the flavanone naringenin and the disaccharide neohesperidose, [11] is identified as a marker phytochemical in the plant Drynaria quercifolia (L.) J. Sm.…”
Section: Resultsmentioning
confidence: 99%
“…[7] So chromatographic fingerprints with biomarker helps in accurate authentication as well as quality of the plants. [8] Even though high-performance liquid chromatography (HPLC) and high-performance thin-layer chromatography (HPTLC) methods of extracts from the rhizome of this plant is reported in the literature, there is no HPTLC method of aqueous extract with marker compound naringin. [3], [9] Thus the present study is aimed at development of HPTLC finger printing profile of aqueous extract of rhizome of Drynaria quercifolia (L.) J. Sm.…”
Section: Introductionmentioning
confidence: 99%
“…It is verry difficult to identify correct marker compounds for all traditional medicinal, but using chromatographic fingerprint, the authencation and identification of herbal medicines can be accurately conducted. 25 Therefore, the use of markers and chromatographic fingerprinting techniques can give useful information assisting manufacturing control, minimising variations in production batches and assuring batch to bacth consistency, with reproducible results. 26 As shown in Figure 5, TLC profiles showed that the R f value of all samples extract at 0.51 (M2) equal to the standard quercetin.…”
Section: Application Of Tlc In Analysis Of Phytochemical Profiling Ofmentioning
confidence: 99%
“…The analytical technique selected is specific and solution stable, provides linearity of 0.999 and 99.24% of sample. 1,[33][34][35] Thus, the results depicted in TLC and HPTLC experimentation played a vital role in our research helping us to identify the β-sitosterol with their percentage in the plant extracts.…”
Section: 27-32mentioning
confidence: 99%